2002
DOI: 10.1021/jf011219f
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Azoxystrobin, Pyrimethanil, Cyprodinil, and Fludioxonil on Tomatoes in a Greenhouse

Abstract: The disappearance of azoxystrobin, pyrimethanil, cyprodinil, and fludioxonil on tomatoes in greenhouse was studied. At the preharvest interval, except for cyprodinil, the pesticide residues were below the MRL fixed in Italy. The mechanism of disappearance studied with model systems shows that the decrease in residues was due to codistillation and photodegradation in pyrimethanil, to photodegradation in fludioxonil, and to evaporation and codistillation in cyprodinil. Azoxystrobin residues were stable during al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 6 publications
4
78
1
16
Order By: Relevance
“…A constant search for new pesticides is on-going to combat the resistance developed by pests against traditional pesticides. For example, fungicides, such as azoxystrobin, cyprodinil, fludioxonil and pyriproxyfen are relatively new pesticides that have been introduced into the marketplace [1]. However, the fact that agricultural products cannot be sold if they contain pesticides exceeding the residual limit implicates the need for development of methods to effectively eliminate residual pesticides in harvested crops [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A constant search for new pesticides is on-going to combat the resistance developed by pests against traditional pesticides. For example, fungicides, such as azoxystrobin, cyprodinil, fludioxonil and pyriproxyfen are relatively new pesticides that have been introduced into the marketplace [1]. However, the fact that agricultural products cannot be sold if they contain pesticides exceeding the residual limit implicates the need for development of methods to effectively eliminate residual pesticides in harvested crops [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Acetone and petroleum ether are the solvents involved in the published journal references [2,3]. And subsequently it was cleaned up using mini chromatographic columns.…”
Section: Results and Discussion Extraction Solventsmentioning
confidence: 99%
“…Because of the systemic activity of azoxystrobin, it was stable in tomato fruits and there is no any decrease under greenhouse conditions. But it is sensible to sunlight, the photodegradation test showed that the waxes had a stronger screen effect compared to the glass, and its t 1/2 is 9.6 h and 0.9 h, respectively [3]. In a greenhouse study, when the tomato leaves was sprayed with homogenous 0.1% aqueous solution of Amistar 250 SC, it was found that the t 1/2 of azoxystrobin was on the average within 13 days [2].…”
Section: Validation In Tomato and Soil Samples Under Field Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Monadjemi et al (2011) estimated half-life of chlorothalonil due to photodegradation at 5.3 days. There are studies indicating high azoxystrobin stability on tomato leaves within 1-4 days after spraying (Szpyrka & Sadło, 2008) and even after 7-10 days on fruits (Garau et al, 2002). Thus chlorothalonil is more susceptible to physical interactions on leaf surfaces than azoxystrobin.…”
mentioning
confidence: 99%